Influence of roller defect and coupled roller–inner–outer race defects on the performance of cylindrical roller bearing. (September 2019) - Patel, Sachin P; Upadhyay, S H
In the present study, a novel mathematical model is developed for the deformation between roller and races of cylindrical roller bearing using the effect of tilting and skewing of roller due to thrust load, radial deflection due to normal load, radial internal gap, and individual defect on roller as well as coupled defect on all races and roller. Also, novel roller defect function is proposed for the preparation of simultaneous nonlinear equations. MATLAB is used to solve nonlinear equations for equilibrium conditions of deflection, radial load, thrust load, moment in plane, and total roller loading. However, waviness due to surface irregularity on both races as well as out-of-balance assembly is not considered in this analysis. The bearing is analyzed for individual roller defect as well as coupled races–roller defects to identify the behavior of bearing under speed-varying conditions. The equation of motion is solved through Newmark-β technique. Defect segment of roller consecutively in contact with both races results in higher acceleration. Time-to-impact concept is utilized for the analysis. The acceleration during roller–race defect interaction with intermittent connection is applied in the model for observation. The outcomes are shown in the time domain, orbit, and envelope analysis, which describe the complexity of the system with speed variation for roller defect and coupled roller–inner–outer race defects. The periodic, quasi-periodic, and chaotic phenomena are observed for roller and coupled defects. Simulated frequencies for all defects are compared with theoretical frequencies to validate the model.